Research on a Grading Evaluation System for Water Inflow in Three-Hole Parallel Subsea Tunnels Considering Inter-Tunnel Influence - Zhiming Han; Keyu Yan; Zhengguo Zhu; Huimin Cui (Applied Sciences, 2023)
Water inflow analysis is critical for subsea tunnel construction. However, existing studies largely concentrate on the inflow issues pertaining to single-hole tunnels. To address current practical engineering problems, a three-hole parallel configuration is common for subsea tunnels, which may alter water inflow patterns due to the influence of their seepage fields. Herein, numerical simulations are conducted to investigate the water inflow characteristics of a three-hole parallel subsea tunnel. Specifically, the impact of various factors on the water inflow phenomenon, including the permeability coefficient of the surrounding rock, the depth of the seawater, the depth of the tunnel, the spacing between tunnels, and the relative size of the tunnels, are comprehensively studied. Furthermore, based on the principles of the analytic hierarchy process and fuzzy mathematics, an exhaustive assessment framework is developed to evaluate the water inflow of three-hole parallel subsea tunnels. The results indicate that there is a mutual influence between the three parallel tunnels, differing from the predicted water inflow, which is overestimated in a single-hole tunnel model. Therefore, the water inflow assessment for a three-hole parallel subsea tunnel system should account for the inter-tunnel influences. The findings of this study offer valuable insights for the design of waterproofing and drainage systems in three-hole subsea tunnels.